2015
DOI: 10.7224/1537-2073.2013-048
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Theoretical Content of Online Physical Activity Information for People with Multiple Sclerosis

Abstract: This study, which examined quality and coverage of physical activity behavior change techniques described online for people with MS, illustrated that the dissemination of these techniques requires improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…There have been advances in the reporting of BCTs employed within the MS PA literature, although this is limited. Shirazipour and colleagues 22 examined the coverage of BCTs in internet resources about PA for people with MS and coded 20 websites that aimed to provide information on PA. The authors concluded that the coverage of BCTs needs improvements with BCTs such as stress-management and motivational interviewing rarely used.…”
Section: Introductionmentioning
confidence: 99%
“…There have been advances in the reporting of BCTs employed within the MS PA literature, although this is limited. Shirazipour and colleagues 22 examined the coverage of BCTs in internet resources about PA for people with MS and coded 20 websites that aimed to provide information on PA. The authors concluded that the coverage of BCTs needs improvements with BCTs such as stress-management and motivational interviewing rarely used.…”
Section: Introductionmentioning
confidence: 99%
“…People with MS are highly active on social media [ 18 , 19 ]. We have previously shown that the demographics of cohorts of patients with MS identified by their activities on social media correspond well with cohorts identified in other sources, indicating that social media data analysis can be usefully applied to outcomes research [ 12 ].…”
Section: Discussionmentioning
confidence: 99%